The Correlation between Reading Media and Students' Vocabulary MAstery at SMAN 6 Kendari - Sinta, Rahmawati (Journal of Teaching English, 2019)
This study aimed to describe the data of students’ vocabulary test score, data of each questionnaire, and to find out the correlation between each media (book, hand phone, and computer/laptop) and students’ vocabulary mastery. Used Correlational study as the design of study with cluster random sampling in taking sample technique where the population were 5 classes (177 students) and the sample was class XI.IA 1 (36 students). Instrument of this study were vocabulary test and questionnaire, vocabulary test consisted of 90 item test in form of multiple choice, matching, identification, translation, and sentence completion while the questionnaire divided into three kind that were 18 statements for book, 15 statements for hand phone, and for 14 statements computer/laptop. Technique data analysis used SPSS version 16 by beginning validity and reliability test, normality test, and Correlation test. Result of this study showed that between book and students’ vocabulary mastery there was very high correlation but between hand phone and students’ vocabulary mastery there was very low correlation on the other hand, there was a low correlation between computer/laptop and students’ vocabulary mastery.In brief, there are positive significant correlation between book, between hand phone as medium with students’ vocabulary mastery, and computer/laptop as media with students’ vocabulary mastery. The use of media are important to variate learning process especially for new medium but the teacher or students have to use media has high correlation to improve students’ vocabulary mastery intensely.